Are the Baltic countries ready to adopt the Euro?: a generalised purchasing power parity approach - Guglielmo Maria Caporale; Davide Ciferri; Alessandro Girardi (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper focuses on macroeconomic interdependencies between the Euro area and three transition economies (Estonia, Lithuania and Latvia), with the aim of establishing whether the latter are ready to adopt the Euro. The theoretical framework is based on the Generalised Purchasing Power Parity (GPPP) hypothesis, which is empirically tested within a Vector Error Correction (VEC) model. Using both monthly and quarterly data over the period 1993-2005, it is found that GPPP holds for the real exchange rate vis-à-vis the Euro of each Baltic country, reflecting a degree of real convergence consistent with Optimum Currency Area criteria. Further, the adopted joint modelling approach for the real exchange rates of the Baltic region outperforms a number of alternative models in terms of out-of-sample forecasts.
Keywords: C32; E00; F36; 330; Transition economies; Euro area; (generalised) Purchasing Power Parity; transition economies; Euro area; (Generalised) Purchasing Power Parity; Vector Error Corrector models; Europäische Wirtschafts- und Währungsunion; EU-Erweiterung; Euro; Kaufkraftparität; Nordosteuropa